An analysis of Politeness Strategy in Directive Speech Act Used by Malala Yousafzai’s Speeches - Quati, Syidra Al; Zaim, M. (Universitas Negeri Padang, 2024)
AbstractThis research aims to determine the types of directive speech acts and types of politeness strategy used by Malala Yousafzai’s speeches. The method of this research is descriptive qualitative which use to discover the accurate facts by having the proper interpretation. The data was taken from Malala Yousafzai speeches and analized by using the theory of Brown & Levinson (1987). This research found that the types of politeness strategies were divided into four types, namely Positive Politeness, Negative Politeness, Bald on record, and Off-record. The results of the research showed that in directive speech acts there are many utterances which is found 99 utterances. The number of directive speech act frequently used is the request which is found 34 utterances. The least of directive speech used is commanding that consisting of 13 utterances. The most politeness strategy used is positive politeness which can be found 62 utterances. The least of politeness strategy that used is Off-Record consisting of 2 utterances. In conclusion, the most that used in directive speech acts by Malala Yousafzai’s speeches is request which consisting of 34 utterances. So that means the speaker is tend to make request to the audience for purposes to invite them to take action or refrain to do something. The most of politeness strategy in directive speech act used by Malala Yousafzai’s speeches was positive politeness consisting of 62 utterances. It means that the speaker tend to minimize the distance between the audience and speaker.